Utilization of Flours from Hemp Stalks as Reinforcement in Polypropylene Matrix - Ibrahim Kilic; Büşra Avcı; İlkay Atar; Nesrin Korkmaz; Güngör Yılmaz; Fatih Mengeloğlu (BioResources, 2024)
Utilization of hemp stalks (HS) was investigated as filler and maleic anhydride-grafted polypropylene (MAPP) as a coupling agent relative to some mechanical, physical, morphological, and thermal properties of polypropylene (PP) composites. The test sample manufacturing used 10, 15, 20, 25, 30, and 35 wt% of HS and 0 wt% or 3 wt% of MAPP. Test specimens were manufactured by combining extrusion and injection molding processes. Results showed that incorporating filler and MAPP increased the mechanical properties significantly. The utilization of HS filler or MAPP provided an improvement of 11.7% (samples containing 35 wt% HS and 3 wt% MAPP) improvement in tensile strength, 44.2% (samples containing 35 wt% HS and 3 wt% MAPP) in flexural strength, and 60.2% (samples containing 30 wt% HS and 0 wt% MAPP) in impact strength compared to neat PP. The scanning electron microscopy analysis provided visual evidence that MAPP improved adhesion between the filler and the polymer matrix. This study showed that using hemp stalks in composite manufacturing provided good overall properties.